The academic task performance scale: psychometric properties, and measurement invariance across ages, genders and nations - van Zyl, Llewellyn Ellardus; Klibert, Jeff; Shankland, Rebecca; Stavros, Jacqueline; Cole, Matthew; Verger, Nicolas B.; Rothmann, Sebastiaan; Cho, Vincent; Feng, Katherine; See-To, Eric W. K.; Roll, Lara C.; Ghosh, Anindita; et al. (Frontiers in Education, 2024)
Task performance refers to the proficiency with which students perform in academic tasks through making the right choices and completing core tasks central to their academic studies, on time and to specification. We adapted Koopmans et al.’s (2014) task performance scale for use within tertiary education and investigated its psychometric properties, internal consistency and measurement invariance across age, gender and national groups in university students (n=3265). The results showed that a hierarchical ESEM model with one higher-order task performance factor consisting of time management and task efficiency fitted the data best. The TPS exhibited full measurement invariance across gender and age groups, implying that the latent mean scores can be used to determine differences. However, invariance could only partially be established for national cohorts, implying that cross-national comparisons may not be possible. These findings offer preliminary support for the TPS as a valid instrument for gauging students’ academic task performance.